Predatory Functional Response of Harmonia sedecimnotata to Aphis craccivora - Jiaru DENG; Zhiwei LIU; Lizhi HUO; Longhua SUN (Guangdong nongye kexue)
【Objective】The study was conducted to clarify the predation capacity of Harmonia sedecimnotata on Aphis craccivora, with a view to providing a theoretical basis for field control of A. craccivora by H. sedecimnotata.【Method】H. sedecimnotata and A.craccivora were taken as experimental subjects. H. sedecimnotata at different stages and different density gradients of late instar nymphs of A.craccivora were prepared to determine the predatory functional response, search effect and intraspecific interference response of H.sedecimnotata to A.craccivora by indoor predation method and numerical model.【Result】The predatory functional response of 1-4th instar of larvae and adults of H. sedecimnotata conformed to Holling Ⅱ model. The predation amount increased with the increase of prey density. The instant attack rates (a) of 1-4st larvae, female and male adults were 0.824, 0.808, 1.364, 1.139, 1.499, 1.626, the handling time (Th) were 0.060, 0.014, 0.006, 0.003, 0.004, 0.005 d, and the maximum daily predation amounts were 16.667, 71.428, 166.667, 333.333, 250.000 and 200.000, respectively. The predation capacity of 1-4th instar larvae and adults of H. sedecimnotata ranked as (from strong to weak): 4th instar, female adult, male adult, 3rd instar, 2nd instar and 1st instar, respectively. The predation amount of larvae increased with the increase of age. For the 4th larvae, the handling time (Th) was the shortest, the predation capacity(a/Th) was the highest, and the maximum daily predation was the highest. which were 0.003 d, 379.667 and 333.333 aphids, respectively. The search effect of H. sedecimnotata on A.craccivora was decreased with the increase of prey density. The search effect of female was greater than that of male. The effect of the H. sedecimnotata's density on the predatory effect of A. craccivora was consistent with the Hassell model. There was intraspecific interference among adult H.sedecimnotata, and the interference equations of female and male adults were E=0.465P-0.515 and E=0.366P-0.505, respectively. The average predation rate decreased with the increase of prey density, the intensity of scramble competition increased with the increase of prey density, and the prey killed by per predator decreased with the increase of predator density. When the predator density reached 5 individuals per plate, the predation rates of female and male adults was the lowest, which were 0.198 and 0.172, and the intensity of scramble competition was the highest, which were 0.548 and 0.558, respectively.【Conclusion】H. sedecimnotata, with a strong predatory ability on the A. craccivora, is an important natural enemy in the biological control of A. craccivora. In practical application, suitable insect state and quantity should be adopted according to the occurrence density of A. craccivora.